2022
DOI: 10.3390/ijms23147824
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine Resistance in Pancreatic Ductal Carcinoma Cell Lines Stems from Reprogramming of Energy Metabolism

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is associated with poor prognosis because it is often detected at an advanced stage, and drug resistance interferes with treatment. However, the mechanism underlying drug resistance in PDAC remains unclear. Here, we investigated metabolic changes between a parental PDAC cell line and a gemcitabine (GEM)-resistant PDAC cell line. We established a GEM-resistant cell line, MIA-G, from MIA-PaCa-2 parental (MIA-P) cells using continuous therapeutic-dose GEM treatment. MIA-G c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 64 publications
0
17
1
Order By: Relevance
“…This mitochondrial number increase in the GEM‐resistant cell lines likely enhances OXPHOS. Furthermore, OXPHOS capacity was clearly improved, not only in basal respiration but also in terms of reserve capacity and maximal respiration (Figure 2B), which contrasted with Fujiwara et al's results 28 . The reason for the discrepancy is unknown; however, it is possible that the experimental conditions may play a role, because of the large discrepancies in the OCR baselines.…”
Section: Discussioncontrasting
confidence: 50%
See 3 more Smart Citations
“…This mitochondrial number increase in the GEM‐resistant cell lines likely enhances OXPHOS. Furthermore, OXPHOS capacity was clearly improved, not only in basal respiration but also in terms of reserve capacity and maximal respiration (Figure 2B), which contrasted with Fujiwara et al's results 28 . The reason for the discrepancy is unknown; however, it is possible that the experimental conditions may play a role, because of the large discrepancies in the OCR baselines.…”
Section: Discussioncontrasting
confidence: 50%
“…In pancreatic cancer stem cells, the enhancement of OXPHOS with increased mitochondria and high sensitivity to OXPHOS inhibition, and the antitumor effect of metformin, an OXPHOS inhibitor, have also been reported 26,27,34 . However, Fujiwara et al reported that, although the basal respiration of a GEM‐resistant cell line was high, GEM treatment reduced TFAM expression and OXPHOS, resulting in reduced ROS production and contributing to GEM resistance 28 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cell growth was assessed using the 3-(4,5-Dimethylthiazol-2-yl)-5-(3-Carboxymethoxyphenyl)-2-(4-Sulfophenyl)-2 H-tetrazolium (MTS) assay as previously described [ 50 ]. MTS assays were performed using the CellTiter 96 Aqueous One Solution Cell Proliferation Assay kit (Promega Biosciences, Inc., San Luis Obispo, CA, USA).…”
Section: Methodsmentioning
confidence: 99%